Analysis of Land Suitability Level and Efficiency of Corn Farming Business in Kempo District, Dompu - Dedy Maskumambang; Bambang Dipokusumo; L. Sukardi (Jurnal Penelitian Pendidikan IPA, 2021)
The development of corn plants should pay attention to the level of land suitability and the resulting economic value. This study aims to evaluate the level of land suitability and efficiency of corn farming in Kempo District so that the results can be used as a reference in making agricultural decisions, especially for the development of corn plants. The research was conducted in the Kempo District, Dompu Regency, West Nusa Tenggara. The research method used is a survey method. The results showed that there was corn farming land cultivated in the land suitability class that was not suitable (N) of 9.30 ha (0.05%), according to marginal (S3) covering an area of ​​8,634.94 ha (45.05%), sufficient suitable (S2) covering an area of ​​6,841.55 (35.70%) and very suitable (S1) covering an area of ​​1,086.59 (5.67%). Corn farmers who cultivate land for corn farming in land suitability class N, farmers incur costs that are higher than the total revenue from corn, the average respondent loses, this is not realized by the farmers concerned, while the highest level of farming efficiency is shown in exploitation land class is very suitable (S1) followed by class S2 and then S3. Based on the results of this study, it is recommended that farmers not cultivate corn on land that is categorized as unsuitable, while on land that is categorized as quite suitable (S2) and marginally suitable (S3), land engineering efforts are needed according to their respective limiting factors to increase the level of suitability be more suitable. While the highest level of farming efficiency was shown in the very appropriate class (S1), followed by the S2 class and then the S3 class